LEGAL MEASURES TO REGULATE THE MASS MEDIA - Vitoonpanyakul, Piboon; Tansiri, Praseart; Vorathanatchakul, Thanakrit (Academic Journal Phranakhon Rajabhat University, 2022)
This Research aimed to educate the theory about Mass Media; how to regulate the Mass Media and Problem of using law to regulate Mass Media. Contrastive Study of Thai’s Law and Others Country’s Law, including to develop the suitable Law for Thai Mass Media.